How Diversity Approaches Affect Ethnic Minority and Majority Adolescents: Teacher–Student Relationship Trajectories and School Outcomes. Issue 1 (12th August 2020) - Baysu, Gülseli; Hillekens, Jessie; Phalet, Karen; Deaux, Kay
Abstract : This study aimed to relate school diversity approaches to continuity and change in teacher–student relationships, comparing Belgian‐majority ( N = 1, 875, M age = 14.56) and Turkish and Moroccan‐minority adolescents ( N = 1, 445, M age = 15.07). Latent‐Growth‐Mixture‐Models of student‐reported teacher support and rejection over 3 years revealed three trajectories per group: normative‐positive (high support, low rejection) and decreasing‐negative (moderate support, high‐decreasing rejection) for both groups, increasing‐negative (moderate support, low‐increasing rejection) for minority, moderate‐positive (moderate support, low rejection) for majority youth. Trajectories differed between age groups. Student and teacher perceptions of equality and multiculturalism afforded, and assimilationism threatened, normative‐positive trajectories for minority youth. Diversity approaches had less impact on majority trajectories. Normative‐positive trajectories were related to improved school outcomes; they were less likely, but more beneficial for minority than majority youth.